Rationale and study design of the REM‐HF study: remote management of heart failure using implanted devices and formalized follow‐up procedures. (18th August 2014) - Morgan, John M.; Dimitrov, Borislav D.; Gill, Jas; Kitt, Sue; Ng, G. Andre; McComb, Janet M.; Raftery, James; Roderick, Paul; Seed, Alison; Williams, Simon G.; Witte, Klaus K.; Wright, D. Jay; et al.
<x xml:space="preserve">Abstract</x> Aims We wish to assess the clinical and cost‐effectiveness of remote monitoring of heart failure patients with cardiac implanted electronic devices. Methods REM‐HF is a multicentre, randomized, non‐blinded, parallel trial designed to compare weekly remote monitoring‐driven management with usual care for patients with cardiac implanted electronic devices (ICD, CRT‐D, or CRT‐P). The trial is event driven, and the final analysis will be performed when 546 events have been observed or the study is terminated at the interim analysis. We have randomized 1650 patients to be followed up for a minimum of 2 years. Patients will remain in the trial up to study termination. The first patient was randomized in September 2011 and the study is expected to complete in early 2016. The primary combined endpoint is time to first event of all‐cause death or unplanned hospitalization for cardiovascular reasons. An economic evaluation will be performed, estimating the cost per quality‐adjusted lifeyear, with direct costs estimated from the National Health Service perspective and quality of life assessed by the EQ‐5D, Short‐Form12, and Kansas City Cardiomyopathy Questionnaires. The study design has been informed by a feasibility study. Conclusion REM‐HF is a multicentre randomized study that will provide important data on the effect of remote monitoring‐driven management of implanted cardiac devices on morbidity and mortality, as well as the cost‐effectiveness of this approach. Trial registration: UKCRN 10383.